"Proceedings of the International Conference, 2004 on Business & Finance, Vol.V: Financial Reporting and Corporate Disclosure Practices" - Amalraj (Hilda) Ed.; Mishra (Chandra Sekhar) Ed. ("52, Nagarjuna Hills,Hyderabad - 500 082", 2005)
Proceedings ; International Conference
50
Keywords: Proceedings ; International Conference